Wskaźniki monitoringu i ewaluacji projektów proekologicznych współfinansowanych z funduszy unijnych - Jefmański, Bartłomiej (The Indices of Monitoring and Evaluating of Environmental Projects Co-Financed from the European Union Funds, 2005)
Both feasibility studies and application forms for financial support of ventures co-financed from the EU funds require defining a certain set of measures which makes it possible to monitor and evaluate an investment project. The aim of this study is to create a set of measures for monitoring and evaluating of environmental ventures. The suggested set of measures was prepared for three different areas of the environment management: the quality of the air, the waste management, and the sewage management.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (3); 2005; nr 1075, s. 69-81